From heart to brain: cognitive potential of propranolol and diltiazem through cholinergic enhancement via butyrylcholinesterase inhibition - Domínguez-Fernández, Celtia; Kumar, Amit; Kumar, Rajnish; Darreh-Shori, Taher (Frontiers in Pharmacology, 2025)
BackgroundButyrylcholinesterase (BChE) has emerged as a promising therapeutic target in the treatment of Alzheimer’s disease (AD), particularly in its later stages when acetylcholinesterase (AChE) activity declines. Drug repurposing offers a strategic approach to identify novel BChE inhibitors among existing FDA-approved compounds.ObjectiveThis study aimed to evaluate the cholinesterase inhibitory potential of propranolol and diltiazem—two widely used cardiovascular drugs—through in silico modelling and in vitro and ex vivo enzyme-inhibition kinetic.MethodsMolecular docking was performed using AutoDock Vina to assess the binding affinity of propranolol and diltiazem to AChE and BChE. In vitro screening and inhibition were measured using a modified Ellman’s assay with human recombinant AChE and plasma-derived BChE. Ex-vivo IC50 and Ki values were determined through kinetic analyses in pooled plasma samples, and inhibition modes were characterized using nonlinear regression models.ResultsBoth propranolol and diltiazem selectively inhibited BChE, with minimal activity against AChE. At 100 μM, BChE inhibition exceeded 80% for both compounds, while AChE inhibition was limited to 18% (propranolol) and 2% (diltiazem). Propranolol exhibited a Ki of 0.19 µM, comparable to the selective BChE inhibitor ethopropazine (Ki = 0.15 µM), and acted as a competitive inhibitor. Diltiazem exhibited a higher Ki of 2.3 µM. These effects were observed at concentrations within or near reported brain levels for propranolol, suggesting potential in vivo relevance.ConclusionPropranolol and diltiazem demonstrate selective BChE inhibition, with propranolol showing potency comparable to established potent BChE inhibitors. Given their established safety profiles and CNS activity, these compounds represent promising candidates for repurposing in the treatment of AD and other cognitive disorders. Further in vivo studies are warranted to explore their therapeutic potential.